2008
DOI: 10.1158/0008-5472.can-07-6752
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial/Cell-Surface Protein p32/gC1qR as a Molecular Target in Tumor Cells and Tumor Stroma

Abstract: A tumor homing peptide, LyP-1, selectively binds to tumorassociated lymphatic vessels and tumor cells in certain tumors and exhibits an antitumor effect. Here, we show that the protein known as p32 or gC1q receptor is the receptor for LyP-1. Various human tumor cell lines were positive for p32 expression in culture, and the expression was increased in xenograft tumors grown from the positive cell lines. Fluorescence-activated cell sorting analyses with anti-p32 antibodies showed that p32-positive cell lines ex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
360
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 309 publications
(376 citation statements)
references
References 42 publications
13
360
3
Order By: Relevance
“…1C). Compared with the MDA-MB-435 tumors, less significant changes in the level of heatmediated p32 expression were observed on C8161 tumors, known as the tumor type that expresses a considerably less amount of p32 compared to MDA-MB-435 tumor (23), over a 24 h period postheating (Fig. S1).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…1C). Compared with the MDA-MB-435 tumors, less significant changes in the level of heatmediated p32 expression were observed on C8161 tumors, known as the tumor type that expresses a considerably less amount of p32 compared to MDA-MB-435 tumor (23), over a 24 h period postheating (Fig. S1).…”
Section: Resultsmentioning
confidence: 97%
“…The LyP-1 peptide has been reported to selectively recognize lymphatics and tumor cells in certain tumor types and subsequently inhibit tumor growth (21,22). Recently, it was found that the p32 or gC1qR receptor, whose expression is elevated on the surface of tumor-associated cells undergoing stress, is the target molecule for the LyP-1pep-tide (23). Thus, we investigated whether the enhanced targeting of LyP-1 relates to upregulation of p32 receptors in the heated tumor.…”
Section: Resultsmentioning
confidence: 98%
“…In an extensive study using combinatorial immunoglobulin libraries and phage display, it was further shown that HABP1 is preferentially overexpressed in adenocarcinoma cells and contributes to the malignant phenotype (44). It has been recently reported that HABP1, particularly its cell surface-expressed form, is a new marker of tumor cells and tumor-associated macrophages/myeloid cells in hypoxic/metabolically deprived areas of tumors (45). HABP1 was identified as the receptor for a tumor-homing peptide, LyP-1, which specifically recognizes an epitope in tumor lymphatics and tumor cells in certain cancers.…”
Section: Discussionmentioning
confidence: 99%
“…The tumor specificity of the peptide and anti-HABP1 antibodies was shown to be a result of the higher expression of total HABP1 and the propensity of malignant and tumor-associated cells to express HABP1 at the cell surface. Hence, it is reasonable to postulate that increased cell surface expression of HABP1 as seen in HepR21 cells may be responsible for its increased tumorigenicity (45).…”
Section: Discussionmentioning
confidence: 99%
“…The attractive feature of Lyp-1 is the ability of this compound to be internalized by tumor cells, which can be explored for drug delivery purposes. (16) Recently, Ruoslahti et al have suggested the internalization mechanism of Lyp-1 is through the known receptor p32 that is present and overexpressed at the tumor cell surface (17).…”
Section: Specific Aim #2: Lyp-1 Targetingmentioning
confidence: 99%